Coordinating Public Good Provision by Mediated Communication - Halonen-Akatwijuka, Maija; Park, In-Uck (American Economic Journal: Microeconomics, 2021)
We examine a setup where two agents allocate a fixed budget between public goods in two areas. The agents may be biased to one area, which is their private information. Without communication, the funds are allocated inefficiently, resulting in gaps and duplication in public good provision. Direct communication between the agents is ineffective and cannot resolve the coordination failure even when the potential biases are negligible. Coordination can be improved by a mediator who filters the information communicated by the agents. Our results can throw light on how to improve coordination of humanitarian aid by an appropriately designed information management system.
Keywords: Coordinating; Public Good; Communication